THE ROLE OF RELIGIONS IN THE SPIRITUALITY AND LIFESTYLE OF THE POPULATION IN CENTRAL ASIA IN THE PRE-ISLAMIC PERIOD (Conferencea, 2023)
In the pre-Islamic period in the Central Asian region, especially in Movaraunnahr, the development of different religions and their social life played an important and positive role. The ancient Turanian land achieved high social and spiritual development due to the strength of its religious beliefs and its statehood as early as 2000 BC. They paid special attention to the preservation and development of their traditions and beliefs.